Triggers for Violent Criminality in Patients With Psychotic Disorders - Sariaslan, Amir (JAMA Psychiatry, 2016)
IMPORTANCE: Absolute and relative risks of violence are increased in patients with psychotic disorders, but the contribution of triggers for violent acts to these risks is uncertain. OBJECTIVE: To examine whether a range of triggers for violent acts are associated with risks of violence in patients diagnosed with psychotic disorders and in individuals without a psychiatric diagnosis. DESIGN, SETTING, AND PARTICIPANTS: Using a sample of all individuals born in Sweden between 1958 and 1988 (N = 3 123 724), we identified patients in the National Patient Register who were diagnosed with schizophrenia spectrum disorders (n = 34 903) and bipolar disorder (n = 29 692), as well as unaffected controls (n = 2 763 012). We then identified, within each subsample, persons who had experienced any of the following triggers for violent acts between January 1, 2001, and December 15, 2013: exposure to violence, parental bereavement, self-harm, traumatic brain injury, unintentional injuries, and substance intoxication. By using within-individual models, we conducted conditional logistic regression to compare the risk of the individual engaging in violent acts in the week following the exposure to a trigger with the risk during earlier periods of equivalent length. All time-invariant confounders (eg, genetic and early environmental influences) were controlled for by this research design and we further adjusted for time-varying sociodemographic factors. MAIN OUTCOMES AND MEASURES: Adjusted odds ratios (aORs) of violent crime occurring in the week following the exposure to a trigger event compared with earlier periods. RESULTS: Among the sample of 2 827 607 individuals (1 492 186 male and 1 335 421 female), all of the examined trigger events were associated with increased risk of violent crime in the week following exposure. The largest 1-week absolute risk of violent crime was observed following exposure to violence (70-177 violent crimes per 10 000 persons). For most triggers, the relative risks did not vary significantly by diagnosis, including unintentional injuries (aOR range, 3.5-4.8), self-harm (aOR range, 3.9-4.2), and substance intoxication (aOR range, 3.0-4.0). Differences by diagnosis included parental bereavement, which was significantly higher in patients with schizophrenia spectrum disorders (aOR, 5.0; 95% CI, 3.0-8.1) compared with controls (aOR, 1.7; 95% CI, 1.3-2.2). CONCLUSIONS AND RELEVANCE: In addition to identifying risk factors for violence, clarifying the timing of the triggers may provide opportunities to improve risk assessment and management in individuals with psychotic disorders.